舌に発生した血管肉腫の1例 - 吉田, 将亜; 矢島, 優己; 竹川, 政範; 佐藤, 栄晃; 荒井, 五織; 谷野, 美智枝 (日本口腔外科学会雑誌, 2022)
Angiosarcoma is a malignant tumor originating from vascular endothelial cells. It is extremely rare in the oral cavity. We described a case of angiosarcoma of the tongue.　A 79-year-old woman presented with a tumor located on the left lateral edge of tongue that measured 11 × 10 × 3mm. The tumor was soft and dark red. A biopsy specimen revealed a vascular malignant tumor. She underwent for radical surgical excision under general anesthesia. Thus, the histopathological diagnosis of the tumor was angiosarcoma. Immunohistochemically it was confirmed with analysis of the specimen revealed positive staining for CD31 antibody. Although postoperative adjuvant therapy was required, the patient denied any treatments because of her advanced age. No recurrence or metastasis has been observed 4 years after surgery. This patient needs to be followed up carefully.